Determinants of customer loyalty for roadside restaurants in Malaysia: a structural equation modeling approach - Al Masud, Md. Abdullah; Haque, Ahasanul; Kabir, SMH; Tor-Kadioglu, Cansu (Southern Academic Publisher, 2021)
Customer loyalty has become a fundamental and crucial focus for any business in the retail food industry. Therefore, every organization concentrating on gaining customer loyalty to extend profits and maintain sustainability within the business arena. This study aims to identify the determinants and their effects on customer loyalty for roadside restaurants in Malaysia. Survey data has been administered using a convenience sample of 248 customers from roadside restaurants located at metropolitan area of Kuala Lumpur and Selangor states in Malaysia. SPSS and AMOS statistical packages were used to validate and test the hypotheses. The study found that customer loyalty is mostly related to the environment of the restaurant and quality of food towards roadside restaurant businesses. Moreover, customer satisfaction fully mediates the relationship between the determinants and customer loyalty. This study contributes to stream an enhanced understanding of the problems and benefits for the roadside restaurant owners to formulate good marketing practices and better customer relationship strategies. Future study can be directed by using other independent variables with a more comprehensive solution.